(untitled) (Ius Novum, 2019)
The objective of the paper is to examine the issue of admissibility of adoption by homosexuals from the perspective of relevant human rights. In this context, it is crucial to establish whether a refusal to give permission to adopt a child solely on the grounds of an applicant’s sexual orientation would constitute a breach of the principle of non-discrimination where the legal system provides for the possibility of applying for adoption by an unmarried individual. Different treatment of homosexual persons with regard to access to adoption is perceived by many scholars as justified considering the principle of the best interest of a child. It seems, however, that this justification lacks sufficient support in scientific research into the influence of upbringing by homosexual persons on the child’s development. Taking into account the European Court of Human Rights case law, it must be recognised that homosexual orientation should not be regarded as a condition that by itself rules out the possibility of adoption, at least in case where a legal system admits such a possibility with regard to single individuals. On the other hand, the legal capacity to adopt a child can be derived neither from the right to respect for one’s private and family life nor from the right to found a family.